Synthesis and Evaluation of Ion Recognition Properties of Schiff base Appended on Hydroxyphenyl-benzimidazole - Anju Nalini, Garg (My University, 2023)
A simple, tailor made, novel chemosensor 3 based on benzimidazole incorporating 2-Hydroxy-1- napthaldehyde was designed and synthesized that showed intramolecular charge transfer (ICT) and Aggregation induced emission (AIE) phenomenon. The photophysical properties of chemosensor 3 were evaluated via colorimetric, UV-vis and fluorescence techniques. Chemosensor 3 displayed absorption band at 355 nm while an emission band at 450 nm and 530 nm (20 µM, H2O). Amongst all the tested anions, the visible color change from dark yellow to light yellow was observed only with CN- addition. Moreover, under UV light, the blue fluorescence of chemosensor 3 was enhanced only in the presence of CN- ion. From the photophysical behavior of chemosensor 3, it was examined that the chemosensor 3 exhibited selective behavior towards CN- ion. The emission bands at 450 nm and 530 nm exhibited blue shift of 40 nm and 120 nm respectively. The fluorescence of 3 was enhanced appreciably with CN- addition and the increased fluorescence was not interfered with any of the other competent ions. Significantly, the detection limit of chemosensor 3 for CN- was evaluated to be 3.3 × 10-7 M with the binding constant value of 2 × 10-3 M-1. Chemosensor 3 formed 1:1 complex with CN- ion as suggested by Job’s plot method.
Keywords: Chemosensor; Benzimidazole; Intramolecular Charge Transfer